2022
DOI: 10.3390/biom12070862
|View full text |Cite
|
Sign up to set email alerts
|

No Association of Hair Zinc Concentration with Coronary Artery Disease Severity and No Relation with Acute Coronary Syndromes

Abstract: Cardiovascular diseases (CVDs) are the leading cause of death worldwide. Although zinc (Zn) was reported to have antioxidant, anti-inflammatory and protective properties in CVDs, its association with coronary artery disease (CAD) is still unclear. As methods commonly used to assess Zn levels in blood and urine do not show the full picture of the microelement supply, in this study, the nutritional status of Zn in patients with angiographically confirmed CAD was assessed using inductively coupled plasma optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Taking into account inconclusive data on the influence of Cu on the cardiovascular system, the main objective of this research was to analyze the association between Cu content in hair and the occurrence of acute coronary syndrome (ACS) in patients with coronary artery disease (stable CAD vs. ACS subgroups). In a recent study, we did not find a significant correlation between the Zn content in the hair and the occurrence of ACS [ 38 ]. Therefore, the Cu/Zn-ratio in hair, which describes the balance between these two elements, was analyzed in a similar way to the Cu content.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Taking into account inconclusive data on the influence of Cu on the cardiovascular system, the main objective of this research was to analyze the association between Cu content in hair and the occurrence of acute coronary syndrome (ACS) in patients with coronary artery disease (stable CAD vs. ACS subgroups). In a recent study, we did not find a significant correlation between the Zn content in the hair and the occurrence of ACS [ 38 ]. Therefore, the Cu/Zn-ratio in hair, which describes the balance between these two elements, was analyzed in a similar way to the Cu content.…”
Section: Introductionmentioning
confidence: 60%
“…Details on the study group are presented in Table 1 and in our previous study [ 38 ]. Differences in Cu and Cu/Zn-ratio between male and female patients, age, and BMI subgroups are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies focusing on zinc and vascular physiology indicated an inverse relationship between dietary zinc intake and carotid intima-media thickness [ 203 , 204 ] or aortic calcification [ 205 ]. A recent study conducted by Dziedzic et al [ 206 ] measured the zinc level of hair samples from 133 CAD patients that were evaluated by angiography. A lower level of zinc was detected in the hair of patients with T2DM and high serum TG concentration.…”
Section: Zinc and Atherosclerosis: Animal And Human Studiesmentioning
confidence: 99%